RGD Peptide-Conjugated Selenium Nanocomposite Inhibits Human Glioma Growth by Triggering Mitochondrial Dysfunction and ROS-Dependent MAPKs Activation - Liu, Wenjian; Su, Jing; Shi, Qiang; Wang, Jinlei; Chen, Xiao; Zhang, Shizhong; Li, Mengkao; Cui, Jie; Fan, Cundong; Sun, Beibei; Wang, Guojun (Frontiers in Bioengineering and Biotechnology, 2021)
Chemotherapy is still one of the most common ways to treat human glioblastoma in clinic. However, severe side effects limited its clinic application. Design of cancer-targeted drugs with high efficiency and low side effect is urgently needed. Herein, silver nanoparticles (Ag NPs) and nano-selenium (Se NPs) conjugated with RGD peptides (Ag@Se@RGD NPs) to target integrin high-expressed glioma were designed. The results found that Ag@Se@RGD NPs displayed stable particle size and morphology in physiological condition, and induced significant integrin-targeted intracellular uptake. Ag@Se@RGD NPs in vitro dose-dependently inhibited U251 human glioma cells growth by induction of cells apoptosis through triggering the loss of mitochondrial membrane potential, overproduction of reactive oxygen species (ROS), and MAPKs activation. However, ROS inhibition dramatically attenuated Ag@Se@RGD NPs-induced MAPKs activation, indicating the significant role of ROS as an early apoptotic event. Importantly, Ag@Se@RGD NPs administration in vivov effectively inhibited U251 tumor xenografts growth by induction of apoptosis through regulation MAPKs activation. Taken together, our findings validated the rational design that Ag-Se NPs conjugated with RGD peptides was a promising strategy to combat human glioma by induction of apoptosis through triggering mitochondrial dysfunction and ROS-dependent MAPKs activation.